N‐Heteroacenes as a New Class of Non‐Fullerene Electron Acceptors for Organic Bulk‐Heterojunction Photovoltaic Devices. Issue 6 (31st May 2017) - Lami, Vincent; Leibold, David; Fassl, Paul; Hofstetter, Yvonne J.; Becker‐Koch, David; Biegger, Philipp; Paulus, Fabian; Hopkinson, Paul E.; Adams, Michael; Bunz, Uwe H. F.; Huettner, Sven; Howard, Ian; et al.
Abstract : Herein, we present the first investigation of N ‐heteroacenes as acceptors in bulk‐heterojunction solar cells. The optical and electronic properties of tetraazapentacene (TIPS‐TAP), triptycenyl‐tetraazapentacene (TIPS‐TAP‐1T), and bistriptycenyl‐tetraazapentacene (TIPS‐TAP‐2T) compounds are characterized by UV‐vis, photothermal deflection, and ultraviolet photoemission spectroscopies. We compare the photovoltaic performance of the N ‐heteroacenes and find that cells with TIPS‐TAP‐2T significantly outperform the other derivatives, achieving a power conversion efficiency of 2.5% without extensive optimization or processing additives. We characterize the morphology and order within the active layer by atomic force microscopy and grazing incidence wide‐angle scattering measurements, and find that blends with TIPS‐TAP result in a gross phase separation driven by its strong crystallization. The substitution with triptycenyl units suppresses this crystallization resulting in amorphous films with a finer intermixing and a smooth surface structure. Finally, we investigate the photophysics of charge separation at the donor/acceptor interface and find that it is fundamentally different from the "conventional" polymer‐fullerene systems. In blends with the tetraazapentacene derivatives, exciton dissociation is relatively slow and charge separation is strongly field dependent. We observe improved charge generation and significantly reduced recombination for TIPS‐TAP‐2T as compared to the other derivatives, which in combination with the improved film microstructure is responsible for the enhanced photovoltaic performance. Abstract : N ‐Heteroacenes are investigated for the first time as non‐fullerene electron acceptors in bulk heterojunction solar cells . Without the use of processing additives or extensive optimization, a promising performance of 2.5% is demonstrated. Surprisingly, the photophysics of charge separation in N ‐heteroacenes is field dependent, making it fundamentally different than what has been previously observed for fullerene acceptors.